Meinong on meaning an truth - Sierszulska, Anna (Phenomenology & mind., 2005)
The study aims at exposing Meinong's ideas that may be of interest to analytic philosophers. It contains all the basic information concerning Meinong's theory of objects with a special focus upon 'objectives', which are Meinong's propositions. Meinong's theory of meaning and his epistemological views are discussed in detail. An outline of his conception of truth, which is classified as firmly realistic, is followed by a review of the critical works touching upon Meinong's epistemological ideas. Finally, Meinong's theory of objects is presented as inspiring the development of Meinongian logics.